Collective versus Individual Property: Tenure Security and Forest Tenure Reforms in China - Stein Holden; Jintao Xu; Xuemei Jiang (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2011)
This study assesses the determinants of forest land allocation to households in the forest tenure reforms in China in the period 1980-2005 using data from three provinces in Southern China; Fujian, Jiang Xi and Yunnan. Furthermore, it assesses the current level of tenure security on forest land and how this tenure security is affected by past and more recent policy changes. A key finding is that issuing of written documentation of forest land rights in form of forest land certificates for a specific time period (30-70 years) enhances tenure security beyond what the otherwise perceived rights to land do
Keywords: Q15; 330; Land rights; forest land; China; tenure reform; collective ownership; individual ownership; tenure security; forest land certificates